Continuous Wavelet Transform of Schwartz Tempered Distributions in S′ ( R n ) - Pandey, Jagdish Narayan; Maurya, Jay Singh; Upadhyay, Santosh Kumar; Srivastava, Hari Mohan (Symmetry (Basel), 2019)
In this paper, we define a continuous wavelet transform of a Schwartz tempered distribution f ∈ S ′ ( R n ) with wavelet kernel ψ ∈ S ( R n ) and derive the corresponding wavelet inversion formula interpreting convergence in the weak topology of S ′ ( R n ) . It turns out that the wavelet transform of a constant distribution is zero and our wavelet inversion formula is not true for constant distribution, but it is true for a non-constant distribution which is not equal to the sum of a non-constant distribution with a non-zero constant distribution.